ANALISIS PENGARUH ORIENTASI FASA PENGUAT PADA MATERIAL SANDWICH KOMPOSIT DI PROGRAM STUDI TEKNIK PESAWAT UDARA SEKOLAH TINGGI PENERBANGAN INDONESIA - Lilies Esthi Riyanti; Ego Widoro; Yudha Nur Cahyo( (Langit Biru: Jurnal Ilmiah Aviasi, 2016)
The composite material is the result of a combination of macroscopic material from two or more different components. Components of the composite in the form of reinforcement and a binder (matrix). The strength and properties of the composite can be obtained from the phase constituent, the composition and geometry of the reinforcing phase. There are differences in the strength of the composite on any kind of orientation in which the determination of this orientation will also affect the level of force against the load received on the composite. After the manufacture of some types of samples with different orientations and then continued testing the strength of each type of sample using standard tests according to testing for composite materials and then be done with the calculation and analysis of the strength and stiffness of each sample. From these results can be obtained from the data that the sample composite reinforcements phase orientation in the direction of loading levels of strength and stiffness of the greatest, while the orientation phase composite samples reinforcements perpendicular to the direction of loading levels of strength and stiffness of the weakest. Therefore, in the manufacture of composite materials need to be considered in determining the composition of each layer orientation in accordance with the direction of the load that will be accepted in order to generate maximum power level in the composite material.